Nexus between Cryptocurrency Markets and Hedge Funds in Period Before and During Russia-Ukraine War - Stefanus Chandra Wibowo; Robiyanto Robiyanto; Andrian Dolfriandra Huruta; Triyanto Triyanto (Media Ekonomi dan Manajemen, 2025)
The purpose of this study is to identify the pre- and post-war impact of the Russia-Ukraine war on the interaction between cryptocurrencies, cryptocurrency hedge funds, and traditional hedge funds. This study provides a deeper understanding of how geopolitical events can affect the behavior of financial markets involving cryptocurrencies and hedge funds. In addition, this study also seeks to fill the knowledge gap that exists in the current literature, specifically with regards to hedge fund strategies during specific geopolitical conflicts. This study utilizes secondary data involving the cryptocurrency hedge fund index, global hedge fund index, and eight proposed hedge fund strategies. The study period runs from February 2018 to July 2023. Granger Causality Test and ARDL used in this study. The finding shows that there is a significant relationship between cryptocurrency hedge funds and conventional hedge funds. Statistical analysis revealed cointegration between cryptocurrency hedge funds and conventional hedge funds, indicating a significant long-term relationship. This study identified a significant impact of changes in market behavior before and after the Russia-Ukraine war on cryptocurrency hedge funds.